Dorsal clock neurons claw their way out to control sleep in Drosophila - Duhart, José Manuel (2022)
The drive to sleep is strongly influenced by time of day, with temporal information conveyed through the circadian clock. In pursuit of the neural mechanisms underlying this process, in this issue of Neuron, Sun et al. identify a novel circuit that links circadian output neurons to sleep-promoting neurons within the mushroom bodies.